Topographical anatomy of the mandibular foramen in the dromedary camels (Camelus dromedarius): an extraoral approach for the inferior alveolar nerve blocks - Al Mohamad, Zakriya; Hamed, Mohamed; Abdellatif, Ahmed; Eldoumani, Haitham; Elshafaey, Elsayed; Abouelnasr, Khaled (Frontiers in Veterinary Science, 2023)
Understanding the clinical anatomy of the head is essential for performing proper inferior alveolar nerve (IAN) block anesthesia to facilitate invasive dental procedures in camels. However, osteometric data related to the IAN in camels are lacking. This study was carried out to accurately locate the mandibular foramen (MF) and the course of the IAN in the camel head and to establish an approach for its localization in clinical practice. To achieve these aims, eight osteometric measurements were used to determine the location of the MF in relation to its surrounding structures in six cadaveric skulls of adult camels. Four camel heads were dissected, and the course of the IAN inside the mandibular canal was studied. In addition, four heads were used as a trial for the extraoral approach to the IAN block using contrast radiographs based on established metric indices. Dissection of the four camel heads revealed that the MF was located near the intersection of two lines passing through the occlusal surface of the mandibular cheek teeth and at the midpoint of the zygomatic process of the temporal bone. Significant differences were not observed between the right and left mandibles. Successful deposition of the contrast medium near the MF was observed in all examined specimens. This study reports a new, simple approach to reaching the IAN at the MF. However, further clinical validation of the proposed technique is required.